2016
DOI: 10.1002/rcr2.206
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant T790M mutation and small‐cell lung cancer transformation after acquired resistance to epidermal growth factor receptor‐tyrosine kinase inhibitor

Abstract: A 70-year-old man was admitted to our hospital with an abnormal chest Xray shadow. Bronchoscopy revealed an adenocarcinoma tumour with an epidermal growth factor receptor (EGFR) exon 19 deletion. Positron emission tomography-computed tomography scanning and magnetic resonance imaging showed advanced stage IV lung cancer. He was treated with erlotinib as a first-line drug, which maintained a clinical response for 16 months. After disease progression, a re-biopsy was done from the tumour in the right lower lobe.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…However, when resistance occurs in the form of a transformation, the T790M-mutation tends not to arise in the same malignancy indicating their rare concurrent pattern. 10 The same reciprocal interaction was explained by Suda et al in their scientific report. They analyzed nine EGFR-TKI-refractory metastatic lesions after a patient died with metastatic NSCLC.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, when resistance occurs in the form of a transformation, the T790M-mutation tends not to arise in the same malignancy indicating their rare concurrent pattern. 10 The same reciprocal interaction was explained by Suda et al in their scientific report. They analyzed nine EGFR-TKI-refractory metastatic lesions after a patient died with metastatic NSCLC.…”
Section: Discussionsupporting
confidence: 60%
“…11 Despite the fact that this is a predominant pattern, Fujita et al have recently reported the concurrent existence of T790M-mutation and a SCLC transformation following TKI-resistance. 10 Additionally, one author proposed the role of SCLC tumor markers (pro-gastrin-releasing peptide and neuron-specific enolase) during a TKI-resistance of SCLC as it might be helpful in early detection of transformation. 12 It is also noteworthy that lung cancer is not the only malignancy involving this transformation.…”
Section: Discussionmentioning
confidence: 99%
“…After the tumors became refractory to afatinib, we detected the EGFR-T790M mutation by liquid biopsy and started osimertinib treatment as the third choice of EGFR-TKI. Although several cases have reported refractory tumors, including the coexistence of EGFR-T790M mutation and SCLC transformation after acquiring resistance to EGFR-TKI [ [10] , [11] , [12] ], this is the first report of metachronous resistances to targeted agents diagnosed by repeated genetic testing and successful sequential therapies for the management of tumor growth. Moreover, to our knowledge, this is also the first report of the detection of EGFR-T790M mutation by liquid biopsy after refractory tumors with SCLC transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Activating mutations in EGFR (epidermal growth factor receptor) and KRAS (a member of the RAS/MAPK pathway) occur in about 10-30% of NSCLC [6]. Although EGFR-Tyrosine kinase inhibitors (TKIs) are an established treatment for patients with a confirmed EGFR mutation [7], most patients develop drug resistance over time [8,9]. Also, patients with a KRAS mutation do not have a targeted therapy available to them [10].…”
Section: Introductionmentioning
confidence: 99%